A simple spectrophotometric quantitative determination of Cilostazol in bulk and pharmaceutical dosage forms using DNPH reagent - Siddappa Anjanappa Kuruba, Prashant Chandrakant Hanamshetty (Journal of Applied Pharmaceutical Science, 2015)
A simple, sensitive, cost effective spectrophotometric method developed and validated for the determination of Cilostazol (CIL), in bulk drug and its pharmaceutical formulations. The method is rely on the formation of a hydrazone with 2,4-dinitrophenylhydrazine (DNPH); the reaction of drug with reagent gives a bright yellow colour. The obtained coloured species absorbance was measured at its absorption maximum (λmax) 355 nm. The Beer’s law has been obeyed in the concentration range 2-20 µg/ml. The optical parameters were calculated as 2.2980x104 (L mol-1 cm-1), 0.0161 (µg/cm2), molar absorptivity and Sandell sensitivity respectively. The analytical parameters of interest LOD and LOQ of the proposed method were calculated 0.1079 (μg/ml), 0.3594 (μg/ml) respectively. All the variables were examined to optimize the reaction conditions. There was no interference observed in the presence of common pharmaceutical excipients. The validity of the method was established by analyzing CIL in its pharmaceutical formulations and critically tested for its accuracy by statistical tests. Good recoveries were obtained by the developed method; the obtained results were critically analyzed and successfully employed for the determination of CIL in its pharmaceutical dosage forms.
Keywords: Cilostazol, DNPH, Spectrophotometry, antiplatelet- agregation, Validation.